STUDENT ENGAGEMENT: UTILISING SUGGESTOPAEDIA IN READING : An Exploratory Study at a Public Junior High School in Bandung) - Dewi, Maria Ratna Paramitha (2015)
Student engagement as the grand topic of this research is a common issue to discuss among teachers. Different teaching and learning methods have been proposed in facilitating the student engagement. Suggestopaedia was chosen for this study considering its characteristics to bring a less-tensed atmosphere for learning. Referring to this issue, this research intended to find out how the students got engaged in the reading activities using Suggestopaedia and their responses to the learning method. It employed exploratory study with classroom observation, students' documents, and questionnaire as the instruments for gathering the data. The participants involved in this research were 30 EFL students in eighth grade at a public junior high school in Bandung. The result shows that Suggestopaedia supported by appropriate materials and activities was capable of facilitating the student engagement in the reading activities as it reduced the classroom anxiety and promoted a more composed classroom situation. Keterlibatan siswa sebagai topik utama dalam penelitian ini merupakan isu yang sudah umum diperbincangan di kalangan para guru. Metode pembelajaran yg berbeda telah banyak ditawarkan demi mefasilitasi hal tersebut. Suggestopaedia dipilih dalam studi ini mengingat karakteristik metode itu sendiri yang mampu mengurangi rasa tegang dalam belajar. Mengacu pada hal tersebut, penelitian ini dimaksudkan untuk mengetahui keterlibatan siswa dalam kegiatan membaca dengan menggunakan Suggestopaedia serta respon mereka terhadap metode tersebut. Penelitian ini merupakan studi eksploratori yang menggunakan observasi kelas, dokumen siswa, dan kuesioner sebagai alat dalam pengumpulan data dengan melibatkan satu kelas berjumlah 30 siswa EFL di tingkat kelas 8. Hasil penelitian ini menunjukkan bahwa Suggestopaedia yang didukung dengan materi dan kegiatan yg sesuai dapat memfasilitasi siswa untuk terlibat dalam kegiatan membaca. Hal itu dikarenakan metode yg digunakan dapat mengurangi rasa tegang serta menciptakan suasana kelas yang lebih terkendali.